Intervención fisioterapéutica para el tratamiento coadyuvante del síndrome de intestino irritable en adultos - Elizalde García, Esther Andrea (2022)
ABSTRACT: The present research work was developed as a bibliographic review to analyze the physiotherapeutic intervention for the adjuvant treatment of irritable bowel syndrome in adults by collecting updated information through specific databases: Google Scholar, PubMed, Physiotherapy Evidence Database (PEDro), and University Repositories; This bibliography was assessed for inclusion using the PEDro scale, which too is included had to have a score of 6 points or more. The information was chosen according to specific inclusion criteria. Keywords such as irritable bowel physiotherapy in adults, irritable bowel physiotherapy techniques, physical therapy against irritable bowel syndrome, the role of the physiotherapist against irritable bowel syndrome, constipation, adjuvant physiotherapeutic treatment in irritable bowel, an irritable syndrome in adults; the languages in which the search was carried out include Spanish and English. At the end of the evaluation and analysis, 35 articles were considered for the final work presentation. According to the articles reviewed, it can be noted that the etiology of IBS is unknown. In addition, it has a more significant presence in the female gender and individuals under 50 years of age, presenting an incidence of 10% to 20% worldwide Gastrointestinal disorder is one of the most frequent diagnoses. Thus, the physiotherapeutic intervention aims to reduce abdominal pain/discomfort, normalize the depositional rhythm and empower the patient to produce changes in shape and lifestyle through physical exercise, yoga, electro-acupuncture, massage, and connective tissue manipulation.